Numerical analysis for stress fields induced by laser trepanning of square-slotted blind holes with and without ultrasonic assistance. (May 2020) - Wang, Houxiao; Xu, Ye; Xu, Guoxiang; Zhou, Wei; Zhu, Sukai; Guo, Qinghu
Highlights: Simulation of stress fields for ultrasonic-assisted laser trepanning is reported. Ultrasonic-assisted laser trepanning of square-slotted hole array is simulated. Ultrasonic-induced transient and residual stress fields are numerically analyzed. Transient stress field is different from corresponding residual stress field. Ultrasonic assistance effectively relieves transient/residual stress on workpiece. Abstract: The numerical simulation on laser trepanning of square-slotted hole and hole array in stainless steel sheets with and without ultrasonic assistance was reported for analyzing the stress fields on the workpieces trepanned. Based on reasonable modification and verification for the established models using corresponding experimental results, the transient and/or residual stress distribution characteristics, which were induced by single hole trepanning and hole array trepanning with and without ultrasonic assistance, were analyzed systematically and numerically using finite element method (FEM) coupled with self-developed subprograms after predicting the transient temperature fields. The influence of ultrasonic assistance on stress reduction was also discussed. It was shown that the distribution characteristics of equivalent von-Mises stress fields on the top surface of laser trepanned workpiece were different from those on its corresponding bottom surface. For laser-trepanned workpieces, the residual stress distribution characteristics predicted after sufficient cooling were different from the corresponding transient stress characteristics simulated without sufficient cooling. As a whole, the ultrasonic assistance resulted in a small change for the distribution trend of the transient/residual stress field predicted, while the influence of ultrasonic-induced softening effect on laser trepanned workpiece was primarily demonstrated by the effective reduction of the stress values.